The oribatid mite superfamily Eutegaeoidea (Acari, Oribatida), with descriptions of new taxa from Australia and New Caledonia and a re-assessment of genera and families - Colloff, Matthew J. (Zootaxa, 2023)
Twenty-four new species of Eutegaeoidea from Australia and New Caledonia are described, and two new genera are proposed. These are Eutegaeus woiwurrung sp. nov., E. nothofagi sp. nov., E. bidhawal sp. nov., E. ptilosus sp. nov., Humerotegaeus carinatus gen. et sp. nov., H. concentricus gen. et sp. nov., Atalotegaeus crobylus sp. nov., Neoeutegaeus torsteini sp. nov., N. melipsilon sp. nov. N. malcolmi sp. nov., N. corniculatus sp. nov. (Eutegaeidae), Compactozetes goongerah sp. nov., C. crenellatus sp. nov. (Compactozetidae) and Pterozetes lawrencei sp. nov. (Pterozetidae) from temperate rainforests in Victoria and Tasmania; Compactozetes bundjalung sp. nov., C. calderi sp. nov., C. duonodulus sp. nov., Sadocepheus remus sp. nov. (Compactozetidae) and Porrhotegaeus githabul sp. nov. (Porrhotegaeidae fam. nov.) from temperate and sub-tropical rainforests of the Great Dividing Range in central and northern New South Wales and southern Queensland, Porrhotegaeus catherinae sp. nov. from scalybark closed forest on Lord Howe Island, Eutegaeus odontatus sp. nov. and Compactozetes pirumorpha sp. nov. from moist upland forest on Norfolk Island and Neseutegaeus wardi sp. nov. and Atalotegaeus deficiens sp. nov. from tropical rainforest and moss forest in New Caledonia. Based on the predominantly Southern Hemisphere distribution of Eutegaeoidea, indicating strong Gondwanan affinities, and the morphology of adults and immatures, this taxon is treated as distinct from the Cepheoidea which has a distribution almost entirely within the Northern Hemisphere. Eutegaeoid species previously described from Australia (Eutegaeus soror P. Balogh, 1985, Atalotegaeus mensarosi J. & P. Balogh, 1983, Neseutegaeus monteithi J. & P. Balogh, 1983, Neoeutegaeus phyllophorus J. & P. Balogh, 1983 and Porrhotegaeus ornatus J. Balogh & Mahunka, 1966) are redescribed based on type material and new distribution records provided. Species have distribution patterns predominantly indicative of short-range endemics associated with remnant Gondwanan rainforest. Neseutegaeus monteithi is recombined with Atalotegaeus Luxton, 1988a. The definitions of genera and families of Eutegaeoidea are revised, and their relationships are reconsidered. Birotegaeus Luxton, 1988a and Pareutegaeus Woolley, 1965 are designated junior synonyms of Eutegaeus Berlese, 1916. Immatures are described for the genera Atalotegaeus, Eutegaeus, Neoeutegaeus Aoki, 1964 and Porrhotegaeus J. Balogh & Mahunka, 1966. Neoeutegaeidae fam. nov. is established for Neoeutegaeus Aoki, 1964 and Humerotegaeus gen. nov., Porrhotegaeidae fam. nov. for Porrhotegaeus and Bornebuschiidae fam. nov. for Bornebuschia Hammer, 1966 and Dicrotegaeus Luxton, 1988 which had previously been placed in Cerocepheidae or Compactozetidae. Eutegaeus aysenensis Ermilov, 2021 and E. queulatensis Ermilov, 2021 from Chile, are recombined with Atalotegaeus. A key is provided to the genera of the eight families of Eutegaeoidea, as recognised herein: Eutegaeidae, Neoeutegaeidae fam. nov., Cerocepheidae, Compactozetidae, Bornebuschiidae fam. nov., Pterozetidae and Porrhotegaeidae fam. nov.